Learning about education - Patrick M. Emerson; Bruce McGough (Institute for the Study of Labor (IZA), 2011)
Limited human capital investment is a common characteristic of low-income countries despite the fact that estimated returns to educational investment in low-income countries are generally higher than in high-income countries. Empirical evidence suggests that income and credit constraints can only account for a small part of this underinvestment. Recent experimental evidence shows that families' misperceptions about the returns to education play a large role in their low investment levels. This paper builds a model of human capital and growth that incorporates an adaptive learning mechanism to capture the way agents form perceptions about returns to education. In an economy where human capital investments have both private and public returns, we find multiple learnable equilibria, including those which are characterized by low investment and low returns. We also find that even when the rational equilibrium corresponds to a high level of human capital investment, the learning mechanism, influenced by the agents' priors and cultural bias, may impart low human capital investment for extended periods. Policies that can speed up the learning process are examined and it is found that faster rates of growth can be achieved through interventions.
urn:nbn:de:101:1-201106202097
Keywords: O40; O15; 330; growth; education; learning